Principal component analysis (PCA) on temporal changes of soil health indicators - Fakher Kardoni (Jurnal Ilmu Pertanian, 2023)
Soil health indicators are related to environmental factors, such as nutrient management, crop practices, different cropping systems, and biodiversity. 14 soil health indicators were measured and compared in our study to clarify the impact of different cropping system on soil quality. The primary comparisons were carried out among perennial plants, annual plants, and cover cropping, with an examination of the tillage system and fertilization taken into account during the analysis. Multivariant analysis recorded that the most promising indicators of soil health that related to soil quality and health were organic carbon (OC), total carbon (TC), followed by fall soil total nitrogen (TN). The main factor for clustering treatments based on indicators was N fertilization according to Euclidean distance that was applied to measure similarity of the groups. Although perennials and cover crops recorded more carbon sequestration and TC improvement, corn crops showed the worse impact on soil pH and bulk density (BD). Non-tillage practices significantly increased wet aggregate and soil moisture. The combination of TC field measurements with long-term cropping systems information has improved our understanding of how different cropping practices influence SOC improvement in soil full profile. It would develop appropriate and cost-effective agricultural management activities, maintain or improve carbon soil accumulation to guide farmer decision making, and ultimately advance food and nutritional security.